2023
DOI: 10.3390/molecules28062482
|View full text |Cite
|
Sign up to set email alerts
|

High Value Utilization of Waste Wood toward Porous and Lightweight Carbon Monolith with EMI Shielding, Heat Insulation and Mechanical Properties

Abstract: With the increasing pollution of electromagnetic (EM) radiation, it is necessary to develop low-cost, renewable electromagnetic interference (EMI) shielding materials. Herein, wood-derived carbon (WC) materials for EMI shielding are prepared by one-step carbonization of renewable wood. With the increase in carbonization temperature, the conductivity and EMI performance of WC increase gradually. At the same carbonization temperature, the denser WC has better conductivity and higher EMI performance. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…This was attributed to evenly distributed Cu on the surface of the fiber. Ma et al [62] developed 2 mm carbonized wood-derived carbon (WC) composites using bass, balsa, and beech of three different densities at 600 °C, 800 °C, and 1000 °C. They reported that increasing the carbonization temperature has increased the conductivity of the samples and hence increased the SE.…”
Section: Fabric-reinforced Compositesmentioning
confidence: 99%
“…This was attributed to evenly distributed Cu on the surface of the fiber. Ma et al [62] developed 2 mm carbonized wood-derived carbon (WC) composites using bass, balsa, and beech of three different densities at 600 °C, 800 °C, and 1000 °C. They reported that increasing the carbonization temperature has increased the conductivity of the samples and hence increased the SE.…”
Section: Fabric-reinforced Compositesmentioning
confidence: 99%
“…Notably, the interconnections between its cell walls form a unique porous structure, and the abundant hydroxyl groups serve as active sites conducive to chemical modification, creating favorable conditions for MOF growth . Most of the wood-based composite strategies involve alkali treatment with NaOH solution and TEMPO carboxylation of the matrix to enable in situ growth of MOFs within it or physically mixing both components for direct processing into a usable form. , Nevertheless, these composite synthesis methods suffer from low affinity between MOFs and the substrate, and the high hydroxyl group content in the matrix makes the desorption process challenging. Moreover, the use of some toxic chemical reagents restricts their practical application in CO 2 capture. Herein, we propose an environmentally benign method to oxidize the hydroxyl groups in wood sponge (WS) to enhance the binding strength with MOFs, resulting in a dialdehyde WS (DWS).…”
Section: Introductionmentioning
confidence: 99%